A gestão por competências em Universidades Federais : um estudo comparado na perspectiva do campo CTS - Perseguino, Silvana Aparecida (2017)
Considering the social commitment played by the federal universities, as producers of new knowledge, and the training of qualified professionals and researchers able to contribute to the development of the society, this research develop a critical analysis, following the spectrum of the field of studies Science, Technology and Society (STS), regarding the parameters detailed in the Decree no. 5.707, from 2006/02/23, which established the National Policy for Human Resources Development, encouraging the paradigm of competences within the public sector, and some of the implications for the federal universities. The specific objectives are: 1) to draw the panorama regarding implementation of the management by competences model within the federal universities from the perspective of the Human Resources Management area; 2) To develop a comparative study between two institutions located in the State of São Paulo, in order to identify the institutional specificities, structure and parameters adopted by the people management area in its management model; 3) to suggest guidelines for the model of management by competences in universities based on the social commitment approach. The qualitative-quantitative methodology combines exploratory/descriptive and empirical research, following the literature review, survey and case studies, using content analysis to analyze the results. The results seem to demonstrate that the adoption of the management by competences in the context of federal universities is not consolidated and there are challenges to be faced that may contemplate the complexity of the environment of these institutions. It was also possible to identify that the field of STS studies can contribute to construct guidelines that consider the complexity of both, the model and the universe of the federal higher education institutions in general.